Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Cumulative Review: 20



Work Step by Step

$\frac{(2a)^{-1}+(b)^{-1}}{(a)^{-1}+(2b)^{-1}}$ =$\frac{\frac{1}{2a}+\frac{1}{b}}{\frac{1}{a}+\frac{1}{2b}}$ =$\frac{\frac{b+2a}{2ab}}{\frac{2b+a}{2ab}}$ =$\frac{b+2a}{2ab}\div\frac{2b+a}{2ab}$ =$\frac{b+2a}{2ab}\times \frac{2ab}{2b+a}$ =$\frac{b+2a}{2b+a}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.